2020
DOI: 10.1200/go.20.00307
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Chemotherapy-Related Weight Changes, and Disease-Free Survival in Haitian Women With Nonmetastatic Breast Cancer

Abstract: PURPOSE Few studies have explored the relationship between body habitus and breast cancer outcomes in Caribbean women of African ancestry. This study evaluates the association between body mass index (BMI) and disease-free survival (DFS) in a retrospective cohort of 224 female Haitian patients with nonmetastatic breast cancer. PATIENTS AND METHODS BMI was obtained from the medical records and categorized as normal weight (< 25 kg/m2), overweight (25-29.9 kg/m2), and obese (≥ 30 kg/m2). DFS was defined as ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Increased risk of breast cancer‐specific mortality was evident for BMI above 29 kg/m 2 ( P nonlinearity = .02; 34 studies, 13 324 deaths; 27 publications) 57,63‐65,75,78,79,82,86,91,93,95,96,98‐103,106,109,110,118,125,126,128,137 (Figures 2 and 3). The curves for breast cancer recurrence ( P nonlinearity = .71; 47 studies, 28 165 events; 37 publications) 40,41,45,48,51,54,55,59,63‐65,68‐70,72,73,79,83,85,89,94,96,102,104,106,110,112,115,116,119,120,123‐125,130,131,133 and second primary breast cancer ( P nonlinearity = .19; nine studies, 2925 events; seven publications) 58,63,64,87,108,132,138 appeared linear (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Increased risk of breast cancer‐specific mortality was evident for BMI above 29 kg/m 2 ( P nonlinearity = .02; 34 studies, 13 324 deaths; 27 publications) 57,63‐65,75,78,79,82,86,91,93,95,96,98‐103,106,109,110,118,125,126,128,137 (Figures 2 and 3). The curves for breast cancer recurrence ( P nonlinearity = .71; 47 studies, 28 165 events; 37 publications) 40,41,45,48,51,54,55,59,63‐65,68‐70,72,73,79,83,85,89,94,96,102,104,106,110,112,115,116,119,120,123‐125,130,131,133 and second primary breast cancer ( P nonlinearity = .19; nine studies, 2925 events; seven publications) 58,63,64,87,108,132,138 appeared linear (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 97%
“…However, few studies were included in some subgroups leading to wide 95% CIs and limiting the ability to assess/explain heterogeneity. Meta‐regression analyses indicated that tumor invasiveness or stage may partly explain the heterogeneity observed for breast cancer recurrence ( I 2 = 54%), with the studies of invasive and in situ breast cancers showing a higher average positive association (five studies/publications) 55,96,110,112,127 compared with studies with only invasive cancers (50 studies, 41 publications), 40,41,43‐46,48,51,54,56,59,63‐66,68‐70,72,74,79,84,85,88,89,92,94,102,104,106,115,116,120‐125,130,131,136 and the studies of metastatic breast cancers showing inverse associations (eight studies, two publications) 70,121 compared with the positive associations observed for early stage disease cases (27 studies/publications) 41,43,44,46,48,51,54,56,59,63,66,68,69,72,74,79,88,89,94,106,116,120,122‐124,127,130 ( P meta‐regression = .02 and .003, respectively). A similar pattern by tumor stage was observed for all‐cause mortality (30 studies, 28 publications on early stage diseases 41,43,44,46,54,63,66‐68,72,78,79,88,89,91,94,95,98,100,111,116,120,123,125‐127,129,130 ; five studies, three publications on metastatic disease 70,81,105 ; P meta‐regression .14; Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy may lead to weight gain in breast cancer patients (15)(16)(17)(18). In contrast, long-course chemotherapy has greater effects on adipokines, insulin, and insulin-like growth factors and thus increases the risk for abnormally elevated blood glucose.…”
Section: Effect Of Postoperative Chemotherapy On Fasting Blood Glucose In Patients With Invasive Breast Cancermentioning
confidence: 99%
“…DeGennaro et al, (2018) [ 32 ] contend the unavailability of Haitian population data to be able to calculate age-adjusted rates for significant analysis. Body mass index (BMI) did not seem to have an impact on disease-free survival among a cohort of Haitian women with BC where 63% were either overweight or obese [ 58 ]. In the cohort studied by O'Neill et al [ 59 ], 98% of persons were employed before illness, while 89% suffered a loss of income due to BC.…”
Section: Reviewmentioning
confidence: 99%